Pengaruh Model PjBL Dengan Menggunakan Alat Peraga matematika Untuk Peningkatan Hasil Belajar Dan Keaktifan Siswa Kelas V - Arya Aulia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Students in participating in mathematics learning in the classroom often perceive that mathematics is a difficult subject, and many students are uninterested in participating in the lessons, especially in geometry materials at SDN 127 Sekeloa. Additionally, the learning process is still teacher-centered. The learning needed today must be student-centered, meaning students should be more active in their learning.This research aims to determine the impact of using the Project-Based Learning (PjBL) model with the help of mathematical learning tools to improve learning outcomes and student activity in Grade 5 at Sekolah Dasar. This research uses a quantitative approach with an experimental method, specifically a quasi-experimental type of non-equivalent control group design.The subjects of this research were 30 students from class V-A (experiment) and 30 students from class V-B (control) at SDN 127 Sekeloa. The treatment given to class V-A (experiment) was the Project-Based Learning (PjBL) model with the use of mathematical learning tools, and the treatment for class V-B (control) was conventional learning.Data collection techniques used included pretest-posttest and observation sheets. Data analysis was done through normality testing, homogeneity testing, T-test, N-Gain test, and effect size test.The results of this study show that there is an improvement and effect between the control and experimental classes. This is evident from the significance value (sig. 2-tailed) with the T-test of 0.042. Since the probability value is less than 0.05, the null hypothesis (H0) is rejected, meaning there is a difference in the mathematics learning outcomes between students who received the Project-Based Learning model and those who received conventional learning.Therefore, it can be concluded that the use of the Project-Based Learning (PjBL) model with mathematical learning tools has a positive effect on improving learning outcomes and student activity in Grade 5.